Group counseling using motivational interviewing technique: reducing students' academic procrastination - Sulistiyana Sulistiyana; Mufida Istati; Engga Nur Rahmah (Jurnal Konseling dan Pendidikan, 2022)
This research is based on the discovery of academic procrastination behavior experienced by students. The purpose of this study was to analyze the effectiveness of group counseling services using motivational interviewing counseling to reduce academic procrastination in students. The research approach used is quantitative with the type of experimental research and research design non equivalent pretest-posttest group. The research population consisted of 146 students and a sample of 8 students who had high academic procrastination was then divided into 4 students as the treatment group and 4 students as the control group. The data collection instrument used was a questionnaire on the academic procrastination scale. The data analysis technique uses the t-test formula. Based on the results of calculations with the t-test formula that Thit > Ttab (13.61> 2.447) with an error rate of 5% indicates that group counseling services use motivational interviewing effective for reducing academic procrastination in students. The researcher hopes that through this research, especially for counselors, they can apply counselingmotivational interviewing innovatively to students in order to reduce academic procrastination and so that future researchers are expectedFuture research can analyze the level of student academic procrastination based on gender. Implications The results of this study provide evidence thatmotivational interviewing can have an effective effect on reducing academic procrastination in students and can be used as a conceptual and practical reference in the development of future counseling.